Application of large-size boron-containing diamond in electrocatalytic preparation of hydrogen peroxide

By using large-size boron-containing diamond single crystal as anode material, the high cost and slow reaction kinetics problems in electrocatalytic preparation of hydrogen peroxide are solved, high reaction selectivity and stability are achieved, and H2O2 can be continuously generated under high current density , the accumulation amount has been significantly increased and adapted to various environmental conditions.

CN119194468APending Publication Date: 2024-12-27ZHENGZHOU UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411367716.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing electrocatalytic technology has high costs, many by-products, safety hazards and slow reaction kinetics when preparing hydrogen peroxide, and the stability and conductivity of the existing anode materials are insufficient.

Method used

Large-size boron-containing diamond single crystal is used as the working electrode, and grown on a hexagonal top press through high-temperature and high-pressure method, combined with FeNi alloy as metal catalyst and high-purity boron powder as additives to form a catalyst with high reaction selectivity and stability. Used for electrocatalytic oxidation of water to generate H2O2.

Benefits of technology

It achieves high reaction selectivity and stability, and can continuously produce H2O2 for a long time under high current density. The Faraday efficiency reaches 42.09%, and the accumulation amount reaches 2884.92 ppm within 12 hours. The Faraday efficiency fluctuates little in the stability test, which is suitable for various environmental conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194468A_ABST
    Figure CN119194468A_ABST
Patent Text Reader

Abstract

The invention is applicable to the technical field of electro-catalysis, and provides application of large-size boron-containing diamond in electro-catalysis preparation of hydrogen peroxide, electro-catalysis preparation of hydrogen peroxide is carried out in an H-shaped electrolytic bath, and the H-shaped electrolytic bath comprises an anode region, a cathode region, a diaphragm, three electrodes and an electrolyte solution, wherein the three electrodes comprise a working electrode, a counter electrode and a reference electrode, and a large-size boron-containing diamond single crystal is used as the working electrode. According to the embodiment of the invention, the large-size boron-containing diamond single crystal is used as an electrode material, has excellent stability, high reaction selectivity and activity, is suitable for various special conditions, basically has no requirement on environmental conditions, and can realize long-time continuous generation of H2O2 by electrocatalytic oxidation of water under high current density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrocatalysis, and in particular relates to the application of large-sized boron-containing diamond in the electrocatalytic preparation of hydrogen peroxide. Background Art

[0002] H2O2 is a very important chemical. As an efficient and environmentally friendly oxidant, H2O2 has an active oxygen content of up to about 47.1%. Its oxidation decomposition byproducts are only oxygen and water. It has a wide range of uses in sewage treatment, industrial bleaching (paper / pulp), mining processing (extraction and separation of gold, chromium, copper, etc.), chemical oxidation and synthesis of organic compounds. At the same time, H2O2 is also an excellent energy carrier and can be used in fuel cells. In terms of medical disinfection, H2O2 is more environmentally friendly than chlorinated substances (such as hypochlorous acid), and its demand is expected to continue to increase in the future.

[0003] The preparation technology of H2O2 mainly includes anthraquinone oxidation synthesis method, hydrogen-oxygen direct synthesis method and electrochemical synthesis method. To date, the anthraquinone process is still the industrial standard for manufacturing H2O2, and the industrial mass production of H2O2 is still mainly achieved through the anthraquinone oxidation process. However, the total cost of producing H2O2 by the anthraquinone process is relatively high. The complicated reaction steps and the reaction accompanied by a series of side reactions lead to the production of a large number of toxic and harmful by-products during the anthraquinone process. In addition, due to the high concentration of H2O2 synthesized by the anthraquinone process, there are very high safety risks in transportation and storage. For the hydrogen-oxygen direct synthesis method, although it has the advantages of simple reaction process, few by-products and high product purity, this method also requires high-value-added hydrogen as the starting material. At the same time, the high temperature and high pressure reaction conditions make this technology extremely demanding on equipment and production conditions, and the cost is expensive.

[0004] Compared with the above-mentioned synthesis methods, the electrocatalytic synthesis method has attracted widespread attention from researchers due to its advantages such as simple process, green reaction process, and in-situ direct synthesis. This method is suitable for small and medium-sized H2O2 preparation devices, in-situ synthesis and utilization working environments, chemical energy storage of intermittent power such as wind power and photovoltaic power, etc. Among them, the cathode oxygen reduction method based on the two-electron oxygen reduction reaction was developed earlier, but this synthesis method sacrifices the reduction product hydrogen (clean energy with high energy density) of the cathode in the electrochemical process, and a continuous oxygen source supply is required during the reaction process. At the same time, oxygen must be dissolved in water or gas diffusion electrodes. Due to the limited solubility of oxygen in water (25°C, the solubility is ~ 8 mgL at 1 atm), the solubility of oxygen in water is relatively low. −1 ) and a low diffusion coefficient in water (2.1 × 10 −5 cm −2 s −1), resulting in slow reaction kinetics; in contrast, the anodic water oxidation reaction uses only water as a reactant, has a simple process, and has a low cost for raw material sources. While H2O2 is produced at the anode, hydrogen can be produced at the cathode. Therefore, it is generally believed that the synthesis of H2O2 by the anodic two-electron water oxidation reaction is a more ideal technical means for preparing high value-added chemicals H2O2.

[0005] In recent years, a variety of electrocatalysts have been developed in the prior art for anodic oxidation of water to produce H2O2, mainly including metal oxides and carbon-based materials, such as bismuth vanadate, tungsten oxide, tin dioxide, titanium dioxide, calcium stannate, boron-doped diamond film, carbon paper, carbon cloth, etc. In contrast, metal oxides have better stability, but their poor electrical conductivity leads to lower output current density and lower electrocatalytic yield of H2O2; carbon-based materials have unique chemical stability and structural diversity, good electrical conductivity and low cost, such as carbon paper and carbon cloth, which have excellent electrical conductivity and high current density, but the hybrid types of carbon materials lead to poor reaction selectivity. At the same time, carbon paper and carbon cloth have poor stability under electrochemical oxidation conditions. Carbon exists in two crystalline single forms in nature: tetrahedral sp 3 Diamond crystals with carbon-carbon bonds and regular trigonal or lamellar sp 2 Graphite crystals bonded by carbon-carbon bonds, carbon paper and carbon cloth are hybridized in the sp 2 -sp 3 Mixed hybridization has poor stability, but pure diamond is not conductive, and diamond is mostly used to make polycrystalline materials for diamond films, and its properties are uncontrollable; diamond conductivity can be improved by doping boron. Currently, boron-doped diamond (BDD) thin film materials have been developed and utilized as anode materials for electrocatalytic anodic oxidation of water to produce H2O2. However, thin film diamond electrode materials are polycrystalline structures with uncontrollable properties, and need to be deposited on a substrate material, which affects their conductivity and mechanical properties. Summary of the invention

[0006] The purpose of the embodiments of the present invention is to provide the application of large-sized boron-containing diamond in the electrocatalytic preparation of hydrogen peroxide, aiming to solve the problems raised in the above background technology.

[0007] The embodiment of the present invention is achieved by using large-sized boron-containing diamond in the electrocatalytic preparation of hydrogen peroxide.

[0008] Preferably, the electrocatalytic preparation of hydrogen peroxide is carried out in an H-type electrolytic cell, which includes an anode region, a cathode region, a diaphragm, three electrodes, and an electrolyte solution, wherein the three electrodes include a working electrode, a counter electrode, and a reference electrode, and a large-sized boron-containing diamond single crystal is used as the working electrode.

[0009] Preferably, the counter electrode is a Pt sheet, and the reference electrode is a saturated calomel electrode.

[0010] Preferably, the working electrode and the reference electrode are placed in the anode region, a magnetic stirrer is provided in the anode region, the counter electrode is placed in the cathode region, the anode region and the cathode region are separated by a diaphragm, and the diaphragm is a cation exchange membrane.

[0011] Preferably, the electrolyte is a potassium carbonate solution with a concentration of 2M.

[0012] Preferably, the preparation method of large-sized boron-containing diamond comprises the following steps: using FeNi alloy as a metal catalyst and high-purity boron powder as an additive, using a high temperature and high pressure method on a six-sided top press, and using (111) seed crystals as the basic growth surface to grow crystals, so as to obtain large-sized boron-containing diamond single crystals, wherein the size of the large-sized boron-containing diamond single crystals is 5-7 mm.

[0013] Preferably, the metal catalyst is Fe 58 Ni 42 The alloy has an addition ratio of 0.5-5% of the high purity boron powder, and the high temperature and high pressure has a pressure of 5.0-6.0 GPa and a temperature of 1320-1450°C.

[0014] A large-sized boron-containing diamond single crystal provided in an embodiment of the present invention is a very stable two-electron water oxidation catalyst. When used as an electrode material, it has excellent stability, high reaction selectivity and activity, is adaptable to various special conditions, has basically no requirements for environmental conditions, and can achieve electrocatalytic oxidation of water at high current density to continuously produce H2O2 for a long time; In 2M potassium carbonate solution, at a potential of 3.1 V vs RHE, the Faraday efficiency of the reaction for 15 minutes is the highest, reaching 42.09%; at a potential of 3.1 V vs RHE, the material was subjected to a 12-hour stability test using 2M potassium carbonate solution, and the Faraday efficiency fluctuated very little, basically maintaining at around 27%; large-sized boron-containing diamond single crystals can continuously produce H2O2, with an hourly output stable at 240 ppm. In the 12-hour test, the accumulation of H2O2 can reach 2884.92 ppm. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 Optical photograph of a large-sized boron-containing diamond single crystal provided in Example 1 of the present invention; Figure 2 A diagram of a three-electrode system device used for electrochemical testing using a large-sized boron-containing diamond single crystal provided in Example 2 of the present invention; Figure 3A diagram of a device used for long-term stability testing provided in Example 2 of the present invention; Figure 4 A Faraday efficiency diagram of generating H2O2 in a 2M potassium carbonate solution provided in Example 2 of the present invention; Figure 5 A Faraday efficiency diagram of generating H2O2 in a 2M potassium bicarbonate solution provided in Example 2 of the present invention; Figure 6 A graph showing the yield of H2O2 generated in a 2M potassium carbonate solution provided in Example 2 of the present invention; Figure 7 A graph showing the yield of H2O2 generated in a 2M potassium bicarbonate solution provided in Example 2 of the present invention; Figure 8 A graph showing the accumulation of H2O2 generated in a 2M potassium carbonate solution provided in Example 2 of the present invention; Fig. 9 A graph showing the accumulation of H2O2 generated in a 2M potassium bicarbonate solution provided in Example 2 of the present invention; Fig.10 The stability test results of Example 2 of the present invention in a 2M potassium carbonate solution at a potential of 3.3 V vs RHE for 12 h; Fig.11 This is a picture of measuring the H2O2 concentration in the reaction solution using titanyl sulfate UV-visible spectrophotometry at a potential of 3.3 V vs RHE in a 2M potassium carbonate solution provided in Example 2 of the present invention. DETAILED DESCRIPTION

[0016] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0017] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0018] Embodiment 1: A large-sized boron-containing diamond single crystal, the preparation method of which comprises the following steps: The domestic six-sided top press is used, and the metal catalyst used is Fe 58 Ni 42 Alloy, using high-purity boron powder (B) as an additive, the addition ratio is 4%, under a pressure of 5.6GPa and a temperature of 1360℃, using high-quality (111) seed crystals (~1mm) as the basic growth surface to grow larger boron-containing diamond single crystals (BDD) (~5-7 mm) with higher and more uniform boron doping concentration. The crystal photos obtained during the growth are shown in the figure. Figure 1 shown.

[0019] Example 2: Application of large-sized boron-containing diamond single crystal in electrocatalytic preparation of hydrogen peroxide, specifically comprising the following process: like Figure 2 As shown, an H-type electrolytic cell separated by a sodium ion exchange membrane is used for electrocatalytic reaction. A magnetic stirrer is placed in the anode electrolytic cell. 30 mL of prepared electrolyte is added to each of the cathode and cathode electrolytic cells. Then, a working electrode and a reference electrode are placed in the anode electrolytic cell, a counter electrode is placed in the cathode cell, and the lid of the electrolytic cell is closed. A Pt sheet is used as the counter electrode, a saturated calomel electrode is used as the reference electrode, and the large-sized boron-containing diamond single crystal prepared in Example 1 is used as the working electrode. The reaction area of ​​the working electrode is 0.2 cm 2 , the electrolyte uses 2M potassium carbonate aqueous solution to produce hydrogen peroxide.

[0020] Performance Test: The electrochemical test was carried out using the CHI650E workstation. The computer connected to the electrochemical workstation was turned on, and then the electrochemical workstation was turned on. The CHI650E software was opened on the computer, and the settings were made according to the test requirements. The electrode clip of the electrochemical workstation was connected to the corresponding electrode, and the test could be started after the connection. After the test, the concentration of H2O2 in the reaction solution was determined by the titanium oxysulfate UV-visible spectrophotometry, and the steps were as follows: 0.01 M titanium oxide-sulfuric acid hydrate was dissolved in 3 M sulfuric acid, heated and stirred in a water bath until completely dissolved, 1 mL of the above solution was taken, and then 1 mL of the solution was taken from the reactor, the two solutions were fully mixed, and allowed to stand for 10 minutes. Subsequently, the absorbance of the solution at 407 nm was measured by UV-visible spectroscopy, and the concentration of H2O2 was calculated by the change in absorbance. The test process is as follows: 2M potassium carbonate solution is used as the electrolyte, pH value is 12, and performance tests are performed at 5 potentials from 2.5 V vs RHE to 3.3 V vs RHE. The Faraday efficiency of generating H2O2 after 15min, 30min, and 45min of reaction is shown in the figure below. Figure 4 As shown, according to Figure 4 It can be seen that at the potential of 3.1 V vs RHE, the Faradaic efficiency of the reaction for 15 min is the highest, reaching 42.09%, indicating that at this potential, the selectivity of generating H2O2 for 15 min is the best; 2M potassium bicarbonate solution was used as the electrolyte with a pH value of 8.3. Performance tests were performed at five potentials, from 2.5 V vs RHE to 3.3 V vs RHE. The Faraday efficiency of H2O2 generated after 15 min, 30 min, and 45 min of reaction was shown in the figure below. Figure 5 As shown, according to Figure 5It can be seen that at a potential of 2.5 V vs RHE, the Faradaic efficiency of the reaction for 15 min is the highest, reaching 24.14%, indicating that at this potential, the selectivity of generating H2O2 for 15 min is the best; Using 2M potassium carbonate solution as the electrolyte, pH value is 12, performance test was carried out at 5 potentials from 2.5 V vs RHE to 3.3 V vs RHE, and the yield of H2O2 generated after 15min, 30min, and 45min of reaction was detected. Figure 6 As shown, according to Figure 6 It can be seen that the yield increases with the increase of applied potential. At 3.3 V vs RHE potential, the yield of H2O2 generated after 15 min of reaction is 20.79 μmol cm -2 min -1 ; 2M potassium bicarbonate solution was used as the electrolyte with a pH value of 8.3. Performance tests were conducted at five potentials, from 2.5 V vs RHE to 3.3 V vs RHE. The yield of H2O2 generated after 15 min, 30 min, and 45 min of reaction was tested. Figure 7 As shown, according to Figure 7 It can be seen that at a potential of 3.3 V vs RHE, the yield of H2O2 generated after 15 min of reaction was 2.95 μmol cm -2 min -1 ; Using 2M potassium carbonate solution as the electrolyte, pH value is 12, performance test was carried out at 5 potentials from 2.5 V vs RHE to 3.3 V vs RHE, and the accumulation of H2O2 generated after 15min, 30min, and 45min of reaction was detected. Figure 8 As shown, according to Figure 8 It can be seen that it is positively correlated with the reaction time. At a potential of 3.3 V vs RHE, the accumulated amount of H2O2 generated after 45 min of reaction is 177.78 ppm; 2M potassium bicarbonate solution was used as the electrolyte with a pH value of 8.3. The performance test was carried out at 5 potentials from 2.5 V vs RHE to 3.3 V vs RHE. The accumulation of H2O2 generated after 15min, 30min, and 45min of reaction was detected. Fig. 9 As shown, according to Fig. 9 It can be seen that at the potential of 3.3 V vs RHE, the accumulation of H2O2 generated after 45 min of reaction was 19.18 ppm; The stability test was carried out for 12 h at a potential of 3.3 V vs RHE using a 2 M potassium carbonate solution as the electrolyte with a pH of 12. Figure 3 As shown, in Figure 2 Two peristaltic pumps were added to make the solution circulate, which facilitated the performance test of long-term reaction. The results were as follows Fig.10 As shown, according to Fig.10 It can be seen that the large-sized boron-containing diamond single crystal prepared in Example 1 has very good stability. In the test lasting up to 12 hours, the output of H2O2 steadily increased, and the accumulated amount could reach 2884.92 ppm; Using 2M potassium carbonate solution as the electrolyte, pH value is 12, performance test at 3.3 V vs RHE potential, when the concentration of H2O2 in the reaction solution was determined by titanyl sulfate UV-visible spectrophotometry at 15min, 30min, and 45min of reaction, the photos are as follows Fig.11 shown.

[0021] In summary, in 2M potassium carbonate solution, at a potential of 3.1 V vs RHE, the Faradaic efficiency of the reaction for 15 min is the highest, reaching 42.09%, indicating that at this potential, the selectivity of the reaction for 15 min to generate H2O2 is the best. In 2M potassium bicarbonate solution, at a potential of 2.5 V vs RHE, the Faradaic efficiency of the reaction for 15 min is only 24.14%, because carbonate is more strongly adsorbed on BDD than bicarbonate, which indicates that the competitive adsorption of carbonate, bicarbonate, water and hydroxide ions on the catalyst surface may fundamentally affect the catalyst's selectivity for 2e - Selectivity of the two-electron water oxidation reaction of WOR; The BDD material provided in the embodiment of the present invention has particularly good stability and is adaptable to various special conditions with basically no requirements for environmental conditions. At a potential of 3.1 V vs RHE, the material is subjected to a 12-hour stability test using a 2M potassium carbonate solution. It can be seen that the Faraday efficiency of the 12-hour test fluctuates very little, basically maintaining at around 27%; the BDD material can continuously produce H2O2, with an hourly output that is stable at 240 ppm. In the 12-hour test, the accumulated amount of H2O2 can reach 2884.92 ppm.

[0022] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. Application of large-sized boron-containing diamond in the electrocatalytic preparation of hydrogen peroxide.

2. The use according to claim 1, characterized in that: The electrocatalytic preparation of hydrogen peroxide is carried out in an H-type electrolytic cell, which includes an anode region, a cathode region, a diaphragm, three electrodes, and an electrolyte solution, wherein the three electrodes include a working electrode, a counter electrode, and a reference electrode, and a large-sized boron-containing diamond single crystal is used as the working electrode.

3. The use according to claim 2, characterized in that: The counter electrode is a Pt sheet, and the reference electrode is a saturated calomel electrode.

4. The use according to claim 3, characterized in that: The working electrode and the reference electrode are placed in the anode region, a magnetic stirrer is arranged in the anode region, and the counter electrode is placed in the cathode region. The anode region and the cathode region are separated by a diaphragm, and the diaphragm is a cation exchange membrane.

5. The use according to claim 2, characterized in that: The electrolyte is a potassium carbonate solution with a concentration of 2M.

6. The use according to claim 1, characterized in that: The preparation method of the large-sized boron-containing diamond comprises the following steps: using FeNi alloy as a metal catalyst and high-purity boron powder as an additive, using a high-temperature and high-pressure method on a six-sided top press, and using (111) crystal seeds as the basic growth surface to grow crystals, thereby obtaining a large-sized boron-containing diamond single crystal, wherein the size of the large-sized boron-containing diamond single crystal is 5-7 mm.

7. The use according to claim 6, characterized in that: The metal catalyst is Fe 58 Ni 42 The alloy has an addition ratio of 0.5-5% of high purity boron powder, and the high temperature and high pressure has a pressure of 5.0-6.0 GPa and a temperature of 1320-1450°C.